We Nailed it!5 Star's for QS Rating - Nadira Hana, Abdul Hamid (2018)
University Malaysia Pahang (UMP) has officially been ranked five stars for QS Stars Rating on 17 July 2018. QS Stars rating encompasses of assessment for eight categories namely Teaching, Employability, Research, Internationalization, Facilities, Innovation, Inclusiveness and Programme Strength.